Bimbingan Konseling Islam Dengan Metode Al-Hikmah Untuk Memperbaiki Moralitas Remaja - Anggi Fitri Yani; Kusnadi Kusnadi; Selvia Assoboru (Social Science and Contemporary Issues Journal, 2024)
This research discusses "Islamic Guidance Counseling using the Al-hikmah Method to Improve Adolescent Morality". This research aims to improve adolescent morality and find out Islamic counseling guidance using the al-hikmah method to improve adolescent morality. This type of research is field research with a descriptive approach. Data collection tools include interviews, observation and documentation. Meanwhile, data analysis techniques are data reduction, data presentation, and conclusions or verification. The subjects of this research were 12 teenagers aged 12-15 years, heads and supervisors of the Islamic Youth Family at the An-Nashiriin Mosque. The results of this research show that adolescent morality can be seen from their lack of respect and courtesy, their inability to control themselves, and their inability to get used to behaving well in accordance with moral values. After carrying out the Islamic counseling guidance process in 5 meetings. The stages of Islamic counseling guidance using the al-hikmah method to improve adolescent morality are using the initial stage, transition stage, activity stage, and final stage. So that the results obtained are that teenagers are able to be obedient and respectful towards other people, able to communicate well, able to control themselves, and able to get used to behaving well in accordance with moral values and reducing bad behavior towards other people.